BUDAYA ORGANISASI SUATU TINJAUN TEORITIS TERHADAP KEPUASAN KERJA PEGAWAI - Andi Ardasanti (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2016)
The success and failure of an organization is determined by the organizational culture attached to its members, and how to apply the culture in building the organization. Organizational culture affect how employees behave and work, recognizing their work, in collaboration with project partner and look to the future. Success and failure are determined from cultural organizations and their ability to transform themselves to support the objectives of the organization and maintain its viability. Organizations must be able to enhance human resources and strengthen the culture to carry out its function as a maker of meaning and control in shaping attitudes and behavior of employees (Robbins, 2006). Organizational culture can affect the survival of the organization if it is linked organizations' efforts to anticipate the difficulties in adjusting the various external and internal changes and the integration of the internal forces (Schein, 1992). The level of organizational empowerment with respect to the ability of the system defines the organization and procedures to be followed by his staff. The reference level and individual capabilities with regard to comfort those who are able to highly motivated to take the initiative and act without strict procedures, if people like and be able to handle empowerment, and they are in an organization that empowers them, then the organization can be categorized as an adaptive organization